2015
DOI: 10.1038/ng.3398
|View full text |Cite
|
Sign up to set email alerts
|

Virtual microdissection identifies distinct tumor- and stroma-specific subtypes of pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains a lethal disease with a 5-year survival of 4%. A key hallmark of PDAC is extensive stromal involvement, which makes capturing precise tumor-specific molecular information difficult. Here, we have overcome this problem by applying blind source separation to a diverse collection of PDAC gene expression microarray data, which includes primary, metastatic, and normal samples. By digitally separating tumor, stroma, and normal gene expression, we have identified and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

117
2,319
8
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,656 publications
(2,465 citation statements)
references
References 60 publications
117
2,319
8
21
Order By: Relevance
“…The microarray dataset used to examine CYR61 expression analyzed whole-tissue tumor samples that include both cancer and stromal cells (26), suggesting that the PSCs might be a source of CYR61. To determine whether PSCs within the tumor microenvironment secrete CYR61, we examined RNAseq data that analyzed gene expression in PDAC tumors as well as three cell population isolated from the tumor: PSCs, tumor epithelial cells grown in patientderived xenografts (PDXs) and tumor epithelial cells grown in in vitro cell culture (29). Isolated PSCs, identified as α-SMA positive, vimentin positive and EpCam negative (29), expressed significantly higher levels of CYR61 compared with human tumor epithelial cells in patient-derived xenografts or in vitro cell culture ( Figure 4A).…”
Section: Pancreatic Stellate Cells Are a Source Of Cyr61 In The Pdacmentioning
confidence: 99%
See 1 more Smart Citation
“…The microarray dataset used to examine CYR61 expression analyzed whole-tissue tumor samples that include both cancer and stromal cells (26), suggesting that the PSCs might be a source of CYR61. To determine whether PSCs within the tumor microenvironment secrete CYR61, we examined RNAseq data that analyzed gene expression in PDAC tumors as well as three cell population isolated from the tumor: PSCs, tumor epithelial cells grown in patientderived xenografts (PDXs) and tumor epithelial cells grown in in vitro cell culture (29). Isolated PSCs, identified as α-SMA positive, vimentin positive and EpCam negative (29), expressed significantly higher levels of CYR61 compared with human tumor epithelial cells in patient-derived xenografts or in vitro cell culture ( Figure 4A).…”
Section: Pancreatic Stellate Cells Are a Source Of Cyr61 In The Pdacmentioning
confidence: 99%
“…To determine whether PSCs within the tumor microenvironment secrete CYR61, we examined RNAseq data that analyzed gene expression in PDAC tumors as well as three cell population isolated from the tumor: PSCs, tumor epithelial cells grown in patientderived xenografts (PDXs) and tumor epithelial cells grown in in vitro cell culture (29). Isolated PSCs, identified as α-SMA positive, vimentin positive and EpCam negative (29), expressed significantly higher levels of CYR61 compared with human tumor epithelial cells in patient-derived xenografts or in vitro cell culture ( Figure 4A). PDAC samples expressed an intermediate amount, suggesting that the CYR61 from these samples is derived partly from stromal cells present in the samples.…”
Section: Pancreatic Stellate Cells Are a Source Of Cyr61 In The Pdacmentioning
confidence: 99%
“…FOLFIRINOX. Pancreatic PDX models such as the one used in this study have been shown to be highly predictive of relapse after surgery, reflective of patient outcome, genetics, and RNA tumor subtypes (19,20,24). These results suggest that the iontophoretic delivery of FOLFIRINOX may translate to improved clinical outcomes by enhancing the therapeutic index of this drug mixture, allowing for resection of localized and locally advanced pancreatic cancer.…”
Section: Discussionmentioning
confidence: 74%
“…The aim of our study was to evaluate the iontophoretic delivery of FOLFIRINOX for the treatment of localized pancreatic cancer. We evaluated this therapy in xenografts derived from patients with pancreatic cancer, which have been shown to reflect recently defined RNA tumor subtypes in patients, mirror patient outcome, and be highly predictive of clinical response to many targeted agents (19,20). We report the delivery of high levels of the FOLFIRINOX drugs to the tumor, a reduction in systemic exposure of the drugs, and potent tumor regression.…”
mentioning
confidence: 99%
“…Currently, there are a number of promising stromal-targeting approaches under clinical investigation that may potentially groundbreaking. Recent report from Moffitt et al utilized elegant bioinformatics methods to distinguish gene signatures from pancreatic tumor cells and stromal cells that independently predict patient outcome (56). Such advances will help tailor personalized treatments in the future.…”
Section: Resultsmentioning
confidence: 99%